Sports specialization in young male kayakers: Studying the young athlete, sports selection process, performance and equipment set-up - Fernandes, R. A. d. A. D. (Universidatde de Coimbra, 2024)
This Thesis tries to understand the performance of young kayakers, in the different stages of their maturational and sporting development, identifying the explanatory qualities of their competitive success, whether they are related to maturational, anthropometric or equipment aspects. Seeking to offer orientation guidelines for coaches and athletes based on scientific evidence that help in decision making, whether in the creation of programs in the identification, selection, training, physical and performance evaluation of kayakers or in the adequate selection of equipment configuration. This Thesis is written in manuscripts and organized into eight chapters. Chapter I contains a general introduction, while Chapter II generally describes the methods and procedures adopted in the different studies, including the statistical techniques used. Chapter III focuses on the validation of a unit with GPS and an accelerometer device developed for collective field sports, but commonly used by canoeing coaches, which will later facilitate the evaluation of performance in competition and training. The results suggested a high concordance between the GPS-Accelerometer and the video analysis, suggesting that the GPS-Accelerometer unit is an accurate solution for evaluating time and velocity variables and, in terms of assessing the frequency of paddling, it may be even more reliable. than video analysis due to the high data analysis rate. This validation was fundamental in analyzing the performance of the simulated test in study 4 (Chapter VI). Chapter IV includes a study centered on the experience in the modality, the maturation status and its implications on performance. The results seem to suggest that the best performances are obtained by kayakers biologically more mature, with bigger bodies and more years of specific practice, both for U14 and U16. Chapter V comprises a study that investigates the maturational status of young kayakers and includes data on the effects of Relative Age and Constitutive Year. The data showed that the effects of constitutive year and maturational status seem to influence performance in U16. As for the Relative Age Effect, although no statistically significant differences were found in the total sample or in the two evaluated categories, a substantial part of the top ten kayakers in each competitive age group was born between January and June and was of early maturity. Chapter VI contains an investigation through which, analyzing several variables, an attempt is made to find an adequate evaluation battery for the competitive level, also trying to understand the importance of the frequency of paddles for the performance of young kayakers. The results of this study indicate that a specific assessment battery for the U14 should include the shoulder-to-water distance, the shuttle run test and the BESS test, and for the U16, the shoulder-to-water distance, the pull-down test. up and sit-up. In addition, the increase in the frequency of paddling is associated with better performances in the 200 and 500 m in youth canoeing, mainly in the U16 category. Chapter VIII comprises the general discussion, where the results of the various studies that make up this Thesis are summarized. Finally, Chapter IX is devoted to conclusions. With particular emphasis on implications and knowledge transfer, on future research challenges. The studies in this doctoral thesis reinforce the need to adjust training and competition to the specificity of the age groups for which they are intended. Also affirming the importance of creating guidelines and global norms with benchmarks for technical skills and the appropriate marking of performance benchmarks (maximum and minimum) by age group, which must be met, to avoid early specialization. The conclusions can be summarized as: (a) GPS-Accelerometers can considerably reduce the time required for video analysis allowing, quickly and accurately, the analysis of performance in terms of boat speed, paddle frequency, and other estimated variables from these - (such as the displacement per paddle and the cycle index); (b) the interest of creating competitive rankings parallel to the official results based on the classification by biobanding (c); importance of establishing assessment batteries, specific for the age group, and the need to create training programs that provide young kayakers with the ability to perform the paddle technique with maximum efficiency at high gestural frequencies; (d) the use of the equations resulting from this Thesis will help to quickly obtain a configuration for the length of the paddle. The agents involved in youth canoeing are encouraged to review their talent identification and selection process and respective training methodologies.